MENCERMATI PERUBAHAN SOSIAL MASYARAKAT MINANGKABAU MELALUI NOVEL TAMU KARYA WISRAN HADI - Siti Fatimah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This study discusses changes in the value system in West Sumatera, especially those in the relationship between mamak and nephew in the matrilineal kinship system of the Minangkabau people, as portrayed in Wisran Hadi’s novel Tamu. The findings of this research show that there are parallel occurrences between Tamu and the condition of the Minangkabau people who are experiencing changes in the value system, especially in terms of the role of mamak in West Sumatera. The setting of Tamu is during the New Order around the 1990s. Political factors, i.e. development policies, during the New Order have contributed to the changes in this value system.